2000
DOI: 10.1149/1.1393952
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Mechanism of Nickel in Hot, Concentrated H[sub 2]SO[sub 4]

Abstract: Electrochemical techniques, complemented by weight change and ex situ X‐ray spectroscopic measurements, were employed to characterize the corrosion of nickel in concentrated H2SO4 solutions. By use of a rotating cylinder electrode, it was found that corrosion is a mass‐transport controlled process with the convective diffusion of nickel cations from a saturated NiSO4 layer as its rate‐determining step. The oxidizing nature of the acid solution leads to the formation of additional corrosion products includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 28 publications
4
20
0
Order By: Relevance
“…In another related study to the present one, it was found that prior to establishing a steady state, corrosion of nickel immersed in concentrated H 2 SO 4 solutions proceeds with the formation and subsequent dissolution of NiS surface deposit. 10 When present on the surface, NiS establishes a galvanic interaction with the uncovered metal, significantly polarizing the anodic dissolution reaction. Since corrosion is mass-transport-controlled, the resultant corrosion rate is unaffected during the galvanic-induced anodic polarization.…”
Section: Corrosion-june 2004mentioning
confidence: 99%
“…In another related study to the present one, it was found that prior to establishing a steady state, corrosion of nickel immersed in concentrated H 2 SO 4 solutions proceeds with the formation and subsequent dissolution of NiS surface deposit. 10 When present on the surface, NiS establishes a galvanic interaction with the uncovered metal, significantly polarizing the anodic dissolution reaction. Since corrosion is mass-transport-controlled, the resultant corrosion rate is unaffected during the galvanic-induced anodic polarization.…”
Section: Corrosion-june 2004mentioning
confidence: 99%
“…NiGe was initially around 20nm thick and was formed at 400°C onto a thick relaxed Ge layer both Ge 4+ and Ge 0 (corresponding to Ni-Ge or Ge-Ge environment) are identified when the signal penetrates more deeply within the NiGe layer (low angles). The presence of oxidized Ni is evidenced whatever the depth penetration, as well as a peak of sulphur at 169.2eV, which could be associated to the presence of NiSO 4 , according to [14]. Binding Energy (eV) Intensity (counts/s) Figure 4.…”
Section: Strategies For the Selective Removal Of Un-reacted Ni Towardmentioning
confidence: 94%
“…Here, Ge is oxidized into GeO2 which remains undissolved at the NiGe surface, thus protecting the NiGe from etching as SiO2 protects NiSi. On the other side, Ni layer is oxidized into NiSO4, possibly according to the following reaction (13) [14]. However, the main issue of this approach is the rinse step in de-ionized water (DIW), which is able to etch the surface GeO2 and/or NiSO4 and induce a selectivity loss.…”
Section: Strategies For the Selective Removal Of Un-reacted Ni Towardmentioning
confidence: 99%
“…The corrosion resistance of nickel is due to the formation of a passive film on its surface upon exposure to the corrosive media. Many works were conducted to study the passivation of nickel in acidic solutions [1][2][3][4][5]. However, the obtained results showed that nickel establishes a kind of passivity in acidic solutions in which the corrosion current, in the passive potential range, is somewhat higher than those recorded by other passive metals.…”
Section: Introductionmentioning
confidence: 99%